Interactions at nano-bio interfaces - Rakovich, Aliaksandra (Trinity College (Dublin, Ireland). School of Physics, 2011)
The development of new materials that can be integrated into current technologies is one of the most important challenges of today. As a result, fields such as nanotechnology and biotechnology have seen great advances. More recently, a link between these two fields has been established and has resulted in nano-biosciences being considered to be an important economic factor by many. The field of nanobiotechnology continuously test the boundaries and promises many breakthrough results in the near future. The purpose of this work was thus to add to and advance this very promising field with an emphasis on biomolecuies with technologically exploitable properties. In order to achieve this, the interactions between nanomaterials and biomaterials were studied at nanoscale, with further investigations into the effects that these interactions have on the functionalities of biomolecules. Three model systems were chosen for the investigations based on the range of potential applications that they can provide. Semiconductor quantum dots (QDs) were selected as the nanomaterials component in each of these systems.
Keywords: Physics, Ph.D.; Ph.D. Trinity College Dublin